Treasury Single Account and Fund Management in Nigeria: A Perception of Accounting Practitioners in Ado-Ekiti Metropolis - Salman, Ramat Titilayo; Adeseye, Muideen Awodiran (NIU Journal of Humanities, 2017)
Treasury Single Account (TSA) is a constitutional tool that facilitates collection of all government incoming cash in one account through transferring of the open account balances that hold names of the ministries and government departments existed in the Central Bank and the commercial banks into one consolidated account (CRF) while all approved expenditures and trusts are implemented through this account. The high rate of corruption bedeviling Nigeria economy coupled with the recent financial crunch have necessitated operationalization of the constitutional tool (TSA) across government ministries, parastatals, and extra ministerial departments with the sole aims of reducing siphoning of public fund, boosting revenue collection, and ensuring effective fund  management. This study investigates the role of operationalized TSA in fund management by eliciting the opinion of accounting practitioners in Ado-Ekiti metropolis. Descriptive and inferential statistics were used in analyzing the data for the study. The study revealed that operationalized TSA reduces mismanagement of public fund and boost government revenues. It therefore recommended that the government political will in enforcing the TSA operation be sustained to fully harness its benefits. Keywords: TSA, Fund Management, Accountability, & Transparency